RANCANGAN TAPAK PENGOLAHAN LIMBAH CAIR PABRIK MINYAK KAYU PUTIH (Melaleuca cajuputi subsp. Cajuputi Powell) DENGAN REAKTOR HIBRID ANAEROB (Kasus Pabrik Minyak Kayu Putih Gelaran, Gunung Kidul) - Melki - Pobas; Djoko Marsono; Totok Gunawan (Politeknik Pertanian Negeri Kupang, 2020)
ABSTRACTThis research is aimed to study the contamination level of Gelaran Cajuput Oil Plant wastewater, to obtain the design of the treatment site plan, and to recommend the determination of the site plan location. The phases covered pilot field survey to determine the location, measuring the volume and collecting the sample, analizing the process and deciding the treatment system. The results showed the contamination level parameters were acid pH, and high BOD and COD. The appropriate length, width, and depth of chamber units’ dimension and specifications of the treatment yielded were respectively as follows: a) 1.5 m, 1.0 m, and 1.0 m of equalisation; b) 1.5 m, 1.0 m, and 1.0 m of neutralization; c) 1.25 m, 1.06 m, and 1.25 m of anaerobic hybrid reactor; d) 1.5 m, 1.0 m, and 1.0 m of stabilization, and was located on downward to facilitate the effluent flowing by gravitational force merely. Key Words: Cajuput oil, waste water treatment, site plan, anaerobic hybrid reactor